2019
DOI: 10.30442/ahr.0502-19-49
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of Diabetic Ketoacidosis among children with Type 1 Diabetes mellitus at Ile-Ife, Nigeria

Abstract: Background: Diabetic ketoacidosis (DKA) is a life-threatening complication of Diabetes mellitus. There are few reports on the pattern and outcome of DKA in childhood diabetes in Nigeria but none on the diabetic population from Osun State, Nigeria. Objective: To determine the pattern and factors influencing the outcome of children managed for DKA at the Paediatric Endocrinology Unit of the Obafemi Awolowo University Teaching Hospital Complex (OAUTHC), Ile-Ife, Nigeria, over a ten-year period. Methods: A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…Majority of our study population were from lower socioeconomic class, in consonant with the reports from Enugu [14], and Ife [18], South-East and South-west, Nigeria respectively. The latter study reported an inverse relationship between socioeconomic class and the frequency of DKA.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Majority of our study population were from lower socioeconomic class, in consonant with the reports from Enugu [14], and Ife [18], South-East and South-west, Nigeria respectively. The latter study reported an inverse relationship between socioeconomic class and the frequency of DKA.…”
Section: Discussionsupporting
confidence: 89%
“…The clinical features observed are similar to those reported in studies from Nigeria [10,11,14,17], other parts of Africa [1,19], and Asia [5,26,27], with only slight differences, particularly in the order of frequency. Whilst abdominal pain was the commonest symptom in our study, similar to a study in Himalayan, North India [26], polyuria [5,10,14,18], respiratory distress [19,27] and vomiting [27], were the commonest symptoms reported from studies within{10, 14, 18} and outside Nigeria [5,19,27]. Most of the Nigerian studies [10,14,18] set out to study DKA in the newly diagnosed T1D patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Diabetic ketoacidosis was an initial presentation in 65.0% of the patients managed for diabetes. Even though this value is not as high as the values reported by many authors in Nigeria and Africa, 8,9,16,17 it is still higher than what is found in developed countries such as the USA (25.5%) 18 and Sweden (15.2%) 19 and suggests that most patients with diabetes in this environment will present with DKA at the point of diagnosis. It is worthy of note that 83.3% of the patients at LTH centre presented with DKA which is similar to other single centre experiences in Nigeria and Africa.…”
Section: Discussionmentioning
confidence: 52%